Treatment solutions to cure Xylella fastidiosa diseased plants. (20th April 2016) - ,
Abstract: This opinion addresses the question of the efficacy of current treatment solutions to cure Xylella fastidiosa diseased plants, and discusses the experimental treatments under evaluation by two research groups in Apulian olive orchards infected by strain CoDiRO (Complesso del Disseccamento Rapido dell'Olivo). The increasing problems from newly emerging vascular bacterial diseases and the limited success to cure plants from such infections have stimulated numerous studies on treatments with chemical and biological compounds. Under field conditions, various formulations of copper and zinc as spray or root drench are currently used while further options, for example the application of bioactive substances, are at an experimental stage. In Apulia, preliminary results from intensive treatments with such formulations, in combination with the use of good crop management practices, reported more vigorous new growth of diseased trees. However, results provided so far confirmed the continued presence of X. fastidiosa after the treatments under evaluation. This is in agreement with current knowledge that there are no means to cure plants from this bacterial disease, in the sense of eliminating the pathogen from plant tissues. The reported positive response of the treated olive trees is most probably due to the effect of micronutrients and other bioactive compounds that, together with soil cultivation and agronomical practices, improve the vigour of the plants and their resilience to stress caused by bacterial infections. Notwithstanding the preliminary status of these findings, the Panel acknowledged the potentially positive effects of such treatments in prolonging the productive phase of olive trees and their putative relevance for the management of olive orchards, particularly in the containment area where eradication of the pathogen is considered no longer possible. The Panel also concluded that long‐term studies are needed to confirm that the reported positive effects on crop performance can be sustained over many years.